Circulating Tumor Cells: Fluid Surrogates of Solid Tumors - Thiele, J-A; Bethel, K; Králíčková, M; Kuhn, P (Annual review of pathology, 2017)
Evaluation of circulating tumor cells (CTCs) has demonstrated clinical validity as a prognostic tool based on enumeration, but since the introduction of this tool to the clinic in 2004, further clinical utility and widespread adoption have been limited. However, immense efforts have been undertaken to further the understanding of the mechanisms behind the biology and kinetics of these rare cells, and progress continues toward better applicability in the clinic. This review describes recent advances within the field, with a particular focus on understanding the biological significance of CTCs, and summarizes emerging methods for identifying, isolating, and interrogating the cells that may provide technical advantages allowing for the discovery of more specific clinical applications. Included is an atlas of high-definition images of CTCs from various cancer types, including uncommon CTCs captured only by broadly inclusive nonenrichment techniques.
Keywords: nádorové cirkulující buňky; Neoplasms; circulating tumor microemboli; Biomarkers, Tumor; liquid biopsy; prognóza; nádorové biomarkery; zvířata; Humans; fluid biopsy; biomarkers; nádory; Neoplastic Cells, Circulating; metastasis; precision medicine; Prognosis; lidé; Animals